2021
DOI: 10.3390/molecules26165057
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Biosynthesis of Silver Nanoparticles and Antibacterial Activities: Application and Theoretical Perspectives

Abstract: The biosynthesis of silver nanoparticles and the antibacterial activities has provided enormous data on populations, geographical areas, and experiments with bio silver nanoparticles’ antibacterial operation. Several peer-reviewed publications have discussed various aspects of this subject field over the last generation. However, there is an absence of a detailed and structured framework that can represent the research domain on this topic. This paper attempts to evaluate current articles mainly on the biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Numerous review articles based on the antibacterial activity of AgNPs were published previously. There are several shortcomings and gaps in these review articles (see Table ). Most articles report the synthesis, antimicrobial activity, and brief discussion of factors affecting the antimicrobial activity of AgNPs. ,, Some review articles report cytotoxicity of AgNPs accompanying synthesis and antimicrobial activity. ,,,, One review article reports the synthesis, antimicrobial activity, antibiofilm activity (in brief), and cytotoxicity of AgNPs . However, this review article does not report antimicrobial photodynamic therapy and insights related to the role of AgNPs versus the role of silver ions in antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous review articles based on the antibacterial activity of AgNPs were published previously. There are several shortcomings and gaps in these review articles (see Table ). Most articles report the synthesis, antimicrobial activity, and brief discussion of factors affecting the antimicrobial activity of AgNPs. ,, Some review articles report cytotoxicity of AgNPs accompanying synthesis and antimicrobial activity. ,,,, One review article reports the synthesis, antimicrobial activity, antibiofilm activity (in brief), and cytotoxicity of AgNPs . However, this review article does not report antimicrobial photodynamic therapy and insights related to the role of AgNPs versus the role of silver ions in antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…[100][101][102][103]106,107 Some review articles report cytotoxicity of AgNPs accompanying synthesis and antimicrobial activ- ity. 99,100,103,105,108 One review article reports the synthesis, antimicrobial activity, antibiofilm activity (in brief), and cytotoxicity of AgNPs. 103 However, this review article does not report antimicrobial photodynamic therapy and insights related to the role of AgNPs versus the role of silver ions in antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Among them, metal nanomaterials such as silver nanoparticles (AgNPs) have been widely investigated and employed in antibacterial, anticancer therapeutics, diagnostics, drug delivery, biosensing, and other clinical/pharmaceutical applications owing to their small particle size and large surface area. 4–6 Considering the potential application of AgNPs, the preparation of AgNPs has attracted significant attention in recent decades. 7 It has been found that the biological and chemical properties of AgNPs are related to a series of parameters including size, shape, and stability, which depend mainly on the methodology and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Biological methods are less pricey, less toxicity and sustainable for biosynthesis of silver nanoparticles from various microorganisms and plants [8]. Large scale production, easiness, economically feasible nature, and eco-friendliness equaled to the other prevailing approaches such as using fungi and bacteria which would not be possible with the controversial conventional ways for the production of nanoparticles [9].…”
Section: Introductionmentioning
confidence: 99%